Group Solidarity Based on Halal Network Labels: Moral Embeddedness of Agents of PT. HNI HPAI from an Economic Sociology Perspective - Siti Julaeha (International Journal of Social Science and Business, 2023)
The number of consumers of halal products in the world has continued to increase since 2015 until now. For Muslim consumers, halal products are related to their moral and social values. Halal products meet the dietary standards of a devout Muslim. This research is intended to explore and present empirical evidence about group solidarity from the theory of moral embeddedness. It is important to provide empirical illustrations, especially those related to the halal product business network. At the same time, PT can also use empirical evidence. HNI HPAI in developing its business network. This study uses Beckert's perspective to analyze the foreign labor market. This research analyzes the formation of network label-based group solidarity in the moral-based halal product market. Researchers use digital research, namely SNA (Social Network Analysis) and TNA (Textual Network Analysis), as new methodologies. SNA to analyze the actor relation between HNI and Graph Density. TNA to analyze the narrative words of success stories of HNI agents in online media. The findings explain that morals, beliefs, and norms affect group solidarity based on the halal product business network label.